A new species of Meadow Katydid (Orthoptera: Tettigoniidae: Conocephalini) from the Apalachicola River Basin of Florida, USA - Woo, Brandon (Zootaxa, 2024)
Odontoxiphidium apalachicolae, sp. nov., is described from seasonally flooded savannah habitats of the Central Panhandle of Florida. The new species differs from the only other member of the genus, O. apterum Morse, in morphology, coloration, calling song, and habitat. Color variation in O. apterum is also discussed. The new species appears to be a member of a unique insect fauna that is endemic to the Apalachicola River Basin, a well-known refugium and center for speciation in vascular plants. Continued exploration of this area is needed to fully document arthropod diversity in the region.